2003
DOI: 10.1097/00005110-200305000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Registered Nurse Job Satisfaction and Intent to Leave

Abstract: Results supported the influence of nurse attitude on job satisfaction relative to other contributing factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
414
2
15

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 398 publications
(458 citation statements)
references
References 64 publications
27
414
2
15
Order By: Relevance
“…This finding is significant because Bradbury-Jones et al (2011) With this study's findings and additional support found in the literature (Halfer & Graf, 2006;Cho et al, 2006;Larrabee et al, 2003), it behooves preceptors to be more supportive in the areas of empowerment and encouragement. Not only have these concepts been linked to easing the NLRN transition to practice, but they have been linked to increased job satisfaction, increased work effectiveness, and better nurse retention rates (Casey, Suanders, & O'Hara, 2010;Laschinger, Wilk, Cho & Greco, 2009).…”
Section: Research Question Two Research Question Two Examined the Resupporting
confidence: 68%
See 4 more Smart Citations
“…This finding is significant because Bradbury-Jones et al (2011) With this study's findings and additional support found in the literature (Halfer & Graf, 2006;Cho et al, 2006;Larrabee et al, 2003), it behooves preceptors to be more supportive in the areas of empowerment and encouragement. Not only have these concepts been linked to easing the NLRN transition to practice, but they have been linked to increased job satisfaction, increased work effectiveness, and better nurse retention rates (Casey, Suanders, & O'Hara, 2010;Laschinger, Wilk, Cho & Greco, 2009).…”
Section: Research Question Two Research Question Two Examined the Resupporting
confidence: 68%
“…Larrabee et al (2003) found such an environment to be critical in increasing psychological empowerment, another predictor of job satisfaction. Furthermore, Cho, Laschinger, and Wong (2006) found that higher levels of perceived psychological empowerment had a direct effect on NLRNs' commitment to the organization.…”
Section: Background and Significancementioning
confidence: 99%
See 3 more Smart Citations